Urbanistická studie konverze Tomioka Silk Mill, Japonsko - Havlík, Jan (Vysoké učení technické v Brně. Fakulta architektury)
Přádelna hedvábí ve městě Tomioka, výjimečné průmyslové dědictví v Prefektuře Gunma na ostrově Honšu, je čekatelem k zapsání na Seznam světového dědictví Unesco. Bývalá továrna, dokument transferu francouzské technologie a japonské architektury, byla realizována na principu klasického zónování továrny. Konverze továrny na celoměstské funkce se odráží v novém urbanistickém řešení areálu v městském kontextu. Projekt navrhuje a prověřuje řešení funkčních zón pro uživatele a prohlídkových tras pro turisty. Součástí je hodnocení potenciálu továrních objektů, přírodního rámce továrny i funkčních celoměstských vztahů.

The Tomioka Silk Mill, an extraordinary industrial heritage in the Prefecture of Gunma on the Honshu island, is waiting to be included to the List of Unesco (nowadays is only on the List Tentative). Former factory, documenting the integration of French technology and Japonese architecture, was realised on the principle of classical factory zoning. The conversion of the mill, aiming at multiple-municipal functions, is reflected in a new urbanistic conception of the area in the municipal context. The project proposes and checks functional zones for users and sightseeing routes for turists. The part of that is evaluating the potential of the mill objects, of the landscape of the mill and of the functional municipal relations.
Urban Study of conversion of Tomioka Silk Mill, Japan
Keywords: Urbanistická studie konverze Tomioka Silk Mill; Japonsko; Urban Study of conversion of Tomioka Silk Mill; Japan